Trends in Ambulatory Laminectomy in the USA and Key Factors Associated with Successful Same-Day Discharge: A Retrospective Cohort Study. Issue 1 (February 2020) - Soffin, Ellen M.; Beckman, James D.; Beathe, Jonathan C.; Girardi, Federico P.; Liguori, Gregory A.; Liu, Jiabin
Background: Laminectomy is commonly used in the treatment of lumbar spine pathology. Laminectomies are increasingly being performed in outpatient settings, but patient safety concerns remain. Questions/Purposes: We aimed to describe trends in outpatient lumbar laminectomy between 2008 and 2016 and to identify factors associated with successful same-day discharge. Methods: We identified patients who underwent single-level lumbar laminectomy between 2008 and 2016 in the American College of Surgeons' National Surgical Quality Improvement Program database and divided them into two groups according to their admission status, either inpatient or outpatient. Inpatient and outpatient groups were further divided according to actual length of stay (LOS): did not remain in the hospital overnight (LOS = 0) or stayed in the hospital overnight or longer (LOS ≥ 1). We then analyzed patient characteristics and complications for significance and to identify factors associated with successful same-day discharge. Results: We identified 85, 769 patients, 41, 149 classified as outpatient status and 44, 620 as inpatient status. Between 2008 and 2016, the proportion of procedures performed on an outpatient basis increased from 24.1 to 56.74%. Overall, 27.3% of all patients were discharged on the day of surgery, representing 52.8% of outpatients and 3.8% of inpatients. Older age and longer duration of surgery predicted that patients were less likely to have same-day discharge. Patients with a primary diagnosis other than intervertebral disk disorder, Hispanic ethnic background, or an American Society of Anesthesiologists physical status classification of III were less likely to achieve same-day discharge. Patients under the care of orthopedic surgeons (as opposed to neurosurgeons) were more likely to be discharged on the day of surgery. We also found an association between sex and day of discharge, with female patients being less likely to be discharged on the day of surgery. Conclusions: Laminectomy is increasingly being performed in the outpatient setting. Younger, healthier non-Hispanic male patients undergoing uncomplicated surgery have a higher likelihood of successful same-day discharge.